(untitled) (International journal of medical sciences, 2025)
The article examines medical and social factors that affect the health of women of childbearing age, as well as methods of their correction. The emphasis is on identifying the main factors, such as working conditions, level of health care, lifestyle and socio-economic conditions, which have a significant impact on women's health. The results of studies aimed at identifying the relationship between these factors and the overall level of health are presented. The conclusion provides recommendations for improving the health of women of childbearing age, including comprehensive preventive measures and the implementation of effective strategies for social and medical support.